Cell type–specific super-resolution imaging reveals an increase in calcium-permeable AMPA receptors at spinal peptidergic terminals as an anatomical correlate of inflammatory pain. Issue 11 (November 2019) - Woodhams, Stephen G.; Markus, Robert; Gowler, Peter R.W.; Self, Timothy J.; Chapman, Victoria
Abstract : Abstract: Spinal hyperexcitability is a key event in the development of persistent pain, and arises partly from alterations in the number and localization of α-amino-3-hydroxy-5-methyl-4-isoxazole propionate (AMPA)-type glutamate receptors. However, determining precisely where these changes occur is challenging due to the requirement for multiplex labelling and nanoscale resolution. The recent development of super-resolution light microscopy provides new tools to address these challenges. Here, we apply combined confocal/direct STochastic Optical Reconstruction Microscopy (dSTORM) to reveal changes in calcium-permeable subunits of AMPA-type glutamate receptors (GluA1) at identified spinal cord dorsal horn (SCDH) peptidergic axon terminals in a model of inflammatory pain. L4/5 lumbar spinal cord was collected from adult male C57BL/6J mice 24 hours after unilateral hind paw injection of saline or 1% carrageenan (n = 6/group). Tissue was immunolabelled for markers of peptidergic axon terminals (substance P; SP), presynaptic active zones (Bassoon), and GluA1. Direct stochastic optical reconstruction microscopy revealed a 59% increase in total GluA1 immunolabelling in the SCDH in the carrageenan group, which was not detected by confocal microscopy. Cell type–specific analyses identified a 10-fold increase in GluA1 localized to SP + structures, and identified GluA1 nanodomains that scaled with behavioural hypersensitivity, and were associated with synaptic release sites. These findings demonstrate that dSTORM has the sensitivity and power to detect nanoscale anatomical changes in the SCDH, and provides new evidence for synaptic insertion of GluA1 + -AMPA-Rs at spinal peptidergic nociceptive terminals in a model of inflammatory pain. Abstract : Supplemental Digital Content is Available in the Text.Direct stochastic optical reconstruction microscopy identifies increased expression of calcium-permeable glutamate receptors at spinal peptidergic nociceptive terminals as an anatomical correlate of inflammatory pain.